Konsep Pengelolaan Sumber Daya Air Pasca Putusan Mahkamah Konstitusi Nomor 85/PUU-XI/2013 - Aqiel Al Rosyid Noor; Alfian Khunaefi (Fakultas Hukum Universitas Airlangga, 2019)
On 2013 Supreme court nullified Law Number 7 Year 2004 on water resources management, and reenacted Law Number 11 Year 1974 on irrigation. Law Number 7 Year 2004 considered to oppose Constitution because right to utilize water can be given to the private party or individual. Although, right to utilize water by private party have been constituted under Law Number 7 Year 2004 also have been nullified by Supreme Court; however it doesn’t close any possibilities for any private party or individual to be able to manage water resource, because on Law Number 11 Year 1974 constitute that legal entitiy, social enterprise or individual authorize to utilize water and/or water resource with certain requirement through gained permission from government. However, it is question; although Law Number 7 Year 2004 have been nullified but Law Number 11 Year 1974 still in place; though, both Laws constitute similar concept on water utilization.